Do medical cannabis growers attempt to produce cannabis with different cannabinoid concentrations than recreational growers?. Issue 4 (23rd October 2019) - Sznitman, Sharon R.; Barratt, Monica J.; Decorte, Tom; Hakkarainen, Pekka; Lenton, Simon; Potter, Gary; Werse, Bernd; Wilkins, Chris
Abstract : Purpose: It is conceivable that cannabis cultivators who grow for medical purposes aim to improve the therapeutic index of their cannabis by attempting to produce particular concentrations of CBD and/or THC. The purpose of this paper is to examine whether small-scale medical cannabis growers differ from those growing for recreational reasons in terms of self-assessed concentrations of THC and CBD in the cannabis they grow. Design/methodology/approach: Data collection was conducted online from a convenience sample of 268 cannabis growers visiting a popular Israeli cannabis internet forum. χ 2 and Kruskal–Wallis H were used to test bivariate associations between medical and recreational cannabis cultivators in terms of self-assessed cannabinoid concentrations. Findings: In total, 40 percent of cannabis growers reported that they grow for medical purposes. Medical cannabis growers were more likely to report that they thought they knew the cannabinoid concentrations of the cannabis they grew and they reported higher self-assessed concentrations of THC, but not CBD. Originality/value: Compared to recreational growers, medical cannabis growers are more likely to strive to be informed in terms of the content of their cannabis. Medical growers may also be attempting to grow more potent THC but not CBD cannabis.